LARGE SCALE GROWTH AND PHYCOCYANIN PRODUCTION OF SPIRULINA PLATENSIS TISTR 8666 - Jaisai, Nuanjun; Nancha, Sayan (Srinakharinwirot University Journal of Sciences and Technology, 2024)
This research investigated the growth for phycocyanin production in the outdoor environment for 800 L of Spirulina platensis TISTR 8666. The results presented that a high yield of dried-weight biomass of Spirulina platensis TISTR 8666 cultured 14-28 days can be obtained. The dry weight of biomass was more than 0.60 g/L and contained 44.39% of total protein. Main amino acid of this biomass was glutamic acid, aspartic acid and leucine, in the number of 4487.70 mg/100 g, 3012.71 mg/100 g and 2655.52 mg/100 g, respectively. This biomass could not be detected Clostridium perfringens, Escherichia coli, Salmonella spp. and Staphylococcus aureus. Moreover this biomass presented lead and arsenic less than 0.5 mg/k and 0.31±0.07 mg/kg, respectively. This biomass was taken for extraction using 0.1 M potassium phosphate buffer (pH 7.0). The proportion was 1:20 w/v that can be obtained phytocyanin 78%. This crude phytocyanin-extracted can be defined as phytocyanin food grade, due to the purity ratio (A620/A280) was more than 0.7. Bioactivity studies found that crude extract presented phenol compound content 1311.83±1.31 mgGAE. Antioxidant of DPPH and ABTS scavenging effected with IC50 of 0.6532 mg/mL and 2.0290 mg/mL, respectively.